2016
DOI: 10.1007/s00227-016-3046-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, ecology, and molecular biology of a new species of giant larvacean in the eastern North Pacific: Bathochordaeus mcnutti sp. nov.

Abstract: Bathochordaeus mcnutti sp. nov. is described from the mesopelagic northeast Pacific Ocean (Monterey Bay, California, USA). Larvaceans in the genus Bathochordaeus are large, often abundant zooplankters found throughout much of the world ocean, but until recently it was unclear whether more than a single species of Bathochordaeus existed. Using remotely operated vehicles, we have made hundreds of in situ observations, compiled two decades of time-series data, and carefully collected enough specimens to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
1
23
1
Order By: Relevance
“…Backcrossed hatchlings have also been reported, confirming that F1 hybrids are fertile and introgression may be possible 10 , 13 . Despite the confirmed viability of hybrid F1 females, it has been shown that their nests in northern Bahia have a lower success rate of hatching emergence, whilst other reproductive output parameters, such as hatchling production per clutch, clutch frequency and breeding frequency remained similar to the parental species 14 . Furthermore, no negative effect of hybridization was found on hatchling viability 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Backcrossed hatchlings have also been reported, confirming that F1 hybrids are fertile and introgression may be possible 10 , 13 . Despite the confirmed viability of hybrid F1 females, it has been shown that their nests in northern Bahia have a lower success rate of hatching emergence, whilst other reproductive output parameters, such as hatchling production per clutch, clutch frequency and breeding frequency remained similar to the parental species 14 . Furthermore, no negative effect of hybridization was found on hatchling viability 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For both of these "new" animals, it is the detailed video footage, deposited along with the type "specimens, " that provides the vouchers for verification. For large larvacean species, the external feeding filters can be critical criteria for characterization, but these structures are likewise so delicate that they can only be described from in situ observations (Hamner and Robison, 1992;Hopcroft and Robison, 1999;Sherlock et al, 2017).…”
Section: "New" Speciesmentioning
confidence: 99%
“…We used the consensus of the published B. stygius Cox1 sequences KX599267.1 to KX599281.1 from GenBank (Sherlock et al, 2017), to screen the genome and scaffold SCLE01415711.1 (length 10,388 nt) gave a perfect hit. We translated Cox1 from position 8054 to 6522 on the reverse strand, and a partial Cob sequence from scaffold SCLE01415711.1 (2319 to 2963, reverse strand).…”
Section: Bathochordaeus Stygiusmentioning
confidence: 99%
“…Sakaguchi et al (2017) reported that all Oikopleura dioica mitochondrial sequences (AY116609-AY116611 and KF977307) may be contaminations from bacteria or cnidarians, and provided partial sequences for Oikopleura longicauda in the same study. Partial mitochondrial sequences were published for Bathochordaeus and Mesochordaeus species by Sherlock et al (2017). In addition, Naville et al (2019) recently published draft genome for several appendicularian species.…”
Section: Introductionmentioning
confidence: 99%